COMPARATIVE CHARACTERISTICS OF THE DENTAL DISEASES INCIDENCE IN ADOLESCENTS OF POLTAVA AND THE VILLAGE OF BELOZERIE IN THE CHERKASY REGION - Bublii, T.D.; Dubovaia, L.I. (World of Medicine and Biology, 2020)
Socio–economic factors have a direct impact on the dental health of adolescents. Thus, the incidence of caries in senior pupils of the Belozerie village is by 1.49 times higher in comparison with the similar indices in Poltava. Their intensity of the carious process is exceeding the average value of 2.1±0.32 in urban residents by 2.08 times (p0.05). In adolescents of Poltava, with a satisfactory hygienic condition, the incidence of dental occlusion ano, malies is by 20.2% higher than in the rural youth.